Conducting Online Learning on Fine Arts Science Course During COVID-19 Pandemic - Yuan Fang; Meng Xiau (International Journal of Instruction and Smart Education, 2023)
The COVID-19 pandemic forced most of the education institutions in the world to close learning to avoid the spread of the virus. Most of the student population in the world from kindergarten to university level, have stopped their education temporarily. A lot of children, youth, and adults are not attending schools due to the increased spread of COVID-19, but learning should be conducted to enhance student competency. The objective of this paper is to compare the learning method of fine arts science courses that is conducted during the COVID-19 pandemic with the traditional method. The interaction of students and lecturers is conducted through Zoom, and students do their assignment at home. Students’ achievement can be seen after they have done the assignment and make an artwork. Online learning findings showed that students performed at least as well on the outcome tests as traditional learning.